Supporting Science Foundation Year students to construct arguments from multiple documents - Anderson, Caroline M (2024)
This research explores the experiences of students on a Science Foundation Year (Science FY) course when trying to construct arguments about controversial socio-scientific issues using multiple documents. It sought to identify the challenges these students face, design and implement an approach to support them, and explore their experiences and outcomes of this approach. Four factors from the reviewed literature, prior educational experience, disciplinary knowledge and domain-specific beliefs, justification beliefs, and topic interest informed the design principles (DPs) of the intervention. These were: DP1 - Provide students with opportunities to develop their disciplinary knowledge and domain-specific beliefs, DP2 - Allow students to choose topics they are interested in, DP3 – Teach students how to construct arguments, DP4 – Equip students with the cognitive habits needed to engage with multiple documents, and DP5 – Provide positive, timely feedback which motivates students to engage in effortful processing of belief-inconsistent information. These design principles were implemented during workshops and individual tutorials of a compulsory module of the Science FY course, through teaching, learning, assessment, and feedback activities. A design-based research approach was adopted so that the design principles and intervention could be refined based upon student experiences. These experiences were explored using justification belief questionnaires, a piece of reflective writing, and interviews. 25 students in Study 1 participated in the intervention and six interviewees with different patterns of justification beliefs provided in depth feedback. These participants’ experiences of and outcomes from the first iteration of the intervention led to the design principles and their implementation being revised. The amended activities were evaluated during Study 2 the following year with 30 students, of which seven were interviewed. A key finding from this research is that many of the researched students had not yet developed the cognitive habits needed to manage multiple documents and did not allocate enough time, leading some to experience negative affect and adopt maladaptive strategies, such as procrastination. Another is that the abstract nature of the terms associated with components of arguments hindered understanding of argument structure. Participants differed in their responses to designed workshop activities, but the individual tutorials were very well-received. The feedback provided during these tutorials played a vital role in motivating students to persist in the effortful processing of multiple documents. It is proposed that learning how to judge expertise, how to assess the validity of alternative perspectives, and how to use information from documents as evidence in support of claims has the potential to bring about adaptive changes to justification beliefs. These findings enable this research to make contributions to knowledge, methodology, and professional practice.